The Relationship between Medication Adherence and The Quality of Life of Tuberculosis Patients at the Health Center in Lamongan Regency: Hubungan Kepatuhan Minum Obat dengan Kualitas Hidup Pasien Tuberkulosis di Puskesmas Kabupaten Lamongan - Dewi Indah Ayu Ardiyanti Fistalia; Devi Ristian Octavia; Sri Bintang Sahara M.K.N (Akademi Farmasi Surabaya, 2023)
Tuberculosis (TBC) is one of the deadliest infectious diseases in the world. Adherence to TB therapy is critical in achieving successful treatment outcomes, controlling transmission, and preventing the development of TB drug resistance. Compliance with taking antituberculosis drugs is closely related to the patient's quality of life, but the number of cases of recurrence should be a source of thought whether the patient's adherence to taking the drug will have a significant impact on the patient's quality of life. This study aims to analyze the relationship between medication adherence and the quality of life of tuberculosis patients in Lamongan. The research design is a descriptive collaborative with a cross-sectional approach. Sampling by purposive sampling with a total sample of 60 respondents. Compliance with taking medication was obtained through the MARS-5 questionnaire and quality of life using the SGRQ questionnaire. The data obtained were then analyzed with the Chi-Square test. The results showed that 70.0% of respondents had high medication adherence, and 60.0% experienced a good quality of life category. The results of the Chi-Square test showed that there was a relationship between medication adherence and the quality of life of tuberculosis patients at the Lamongan District Health Center. The more obedient the patient is in taking the drug, the better the quality of life.